2005
DOI: 10.1037/0096-1523.31.6.1247
|View full text |Cite
|
Sign up to set email alerts
|

Gender recognition from point-light walkers.

Abstract: Point-light displays of human gait provide information sufficient to recognize the gender of a walker and are taken as evidence of the exquisite tuning of the visual system to biological motion. The authors revisit this topic with the goals of quantifying human efficiency at gender recognition. To achieve this, the authors first derive an ideal observer for gender recognition on the basis of center of moment (J. E. Cutting, D. R. Proffitt, & L. T. Kozlowski, 1978) and, with the use of anthropometric data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
141
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(150 citation statements)
references
References 50 publications
(126 reference statements)
6
141
0
3
Order By: Relevance
“…Since then, it has been reported that humans are able to extract a variety of behaviorally relevant characteristics, including the type of action (Dittrich, 1993;, the identity of the actor Loula, Prasad, Harber, & Shiffrar, 2005), and the actor's gender Pollick, Kay, Heim, & Stringer, 2005;Troje, 2002), emotional state (Dittrich, Troscianko, Lea, & Morgan, 1996;Montepare, Goldstein, & Clausen, 1987), and age (Montepare & Zebrowitz-McArthur, 1988). Only more recently, however, has the question of how observers interpret the in-depth orientation of point-light figures systematically been addressed (Jackson, Cummins, & Brady, 2008;Vanrie, Dekeyser, & Verfaillie, 2004;Vanrie & Verfaillie, 2006, 2008.…”
mentioning
confidence: 99%
“…Since then, it has been reported that humans are able to extract a variety of behaviorally relevant characteristics, including the type of action (Dittrich, 1993;, the identity of the actor Loula, Prasad, Harber, & Shiffrar, 2005), and the actor's gender Pollick, Kay, Heim, & Stringer, 2005;Troje, 2002), emotional state (Dittrich, Troscianko, Lea, & Morgan, 1996;Montepare, Goldstein, & Clausen, 1987), and age (Montepare & Zebrowitz-McArthur, 1988). Only more recently, however, has the question of how observers interpret the in-depth orientation of point-light figures systematically been addressed (Jackson, Cummins, & Brady, 2008;Vanrie, Dekeyser, & Verfaillie, 2004;Vanrie & Verfaillie, 2006, 2008.…”
mentioning
confidence: 99%
“…In the natural environment, however, perception of the body's shape is rarely decoupled from other body cues, which themselves may also be sexually dimorphic. The body's shape, for example, is generally perceived in motion, and body motion alone informs both basic (26)(27)(28)(29)(30) and evaluative (1,31,32) social judgments. Moreover, the perception of morphological cues as they are typically perceived (in motion) often changes perceptions.…”
mentioning
confidence: 99%
“…Humans reliably classify gender from point-light walkers with a hit rate (correct classification rate) of 65 to 75%; frontal views are classified best [20,25,31]. Studies have focused on cues that mediate gender classification, such as the shoulder-hip ratio [7] or the lateral sway of the upper body that is more pronounced in men [20].…”
Section: Background and Related Workmentioning
confidence: 99%